Is the New Immigration Less Skilled Than the Old? - Chiswick, Barry R. (Journal of Labor Economics, 1986)
This paper analyzes trends in the skills of immigrants to the US in the post-World War II period. Changes in the supply, demand, and institutional factors determining immigration are analyzed for their implications for immigrant skills. During the past 4 decades immigration has shifted from being predominantly European and Canadian in origin to being predominantly Asian and Latin American, and there have been changes in the criteria for rationing immigration visas. Immigrant skills can be analyzed within the context of a model of the supply of immigrants and the US demand for immigrants. Of the Asian immigrants subject to numerical limitation, the proportion who were occupational preference principals declined from 18.2% in 1970, to 11.9% in 1975, to 8.1% in 1981. A growing stock of the foreign-born population who are illegal aliens may lower immigrant quality; for low-skilled workers in neighboring low-income countries the economic incentives for illegal migration are very large. Immigrants from the UK have the highest annual earnings, with Canadian, other European, South Asian, East Asian, and other American immigrants having successively lower earnings. The Mexicans and the Vietnamese have the lowest earnings. Over the period 1950 to 1980, US immigration changed from primarily drawing immigrants from countries whose nationals have high relative earnings in the US primarily drawing immigrants from countries whose nationals do less well. Recent immigrants are less favorably selected on the basis of their level of schooling. The analysis of the relative earnings of immigrants during the 1970s using 3 data files shows there has been little change for white immigrants, an ambiguous pattern for Mexican immgrants, perhaps a small decline for Cuban immigrants, and a small rise for Asian immigrants. Overall, without returning to rationing by country of origin, public policy could raise immigrant skill levels by changing the balance between kinship and the individual's skills in the rationing of visas.